Persediaan Bahan Baku Kedelai dengan Metode EOQ dan POQ di Pabrik Tahu AS Berkah Putra - Dody Chandrahadinata; Ujang Cahyadi; Muhamad Risky Gahara (Institut Teknologi Garut, 2022)
Raw materials become a very important thing in production because if there is a shortage of raw materials it will result in cessation of production or excess raw materials will result in increased storage costs. The purpose of this research is to find out the total cost of raw material inventory using the EOQ (Economic Order Quantity) and POQ (Period Order Quantity) methods and to create scenarios for company inventory planning. Previously, the company placed orders for raw materials with an average of 2319 kg of orders with an order frequency of 48 times a year. The EOQ method can be used at the Berkah Putra AS Tofu factory because it gets a minimum total cost of raw material inventory, which is Rp. 114,672. The frequency of orders in one year is 5 times with a quantity of 5,460 kg of orders. This can minimize costs and control raw material supplies on a regular basis.